2023
DOI: 10.1177/10760296231162079
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Status and Risk of Death After Acute Pulmonary Embolism

Abstract: Background Acute pulmonary embolism (PE) is a heterogeneous disease process with variable presentation and outcomes. The endogenous fibrinolytic system is a complex framework of regulatory pathways that maintains homeostasis by dissolving overabundant thrombi. We sought to investigate phenotypic profiles of the endogenous fibrinolytic system among patients presenting with acute PE and their impact on mortality. Methods We enrolled all consecutive patients with acute PE in our institutional Pulmonary Embolism R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, intermediate-to-high-risk PE patients have significantly longer lysis time than low-and-intermediate-risk PE patients [ 69 ]. High PAI-1, low TAFI, and low α2-antiplasmin indicate a high-risk biomarker profile in acute PE [ 105 ]. This may be of clinical importance when evaluating the results of catheter-based therapy and thrombolysis in PE.…”
Section: Fibrinolysis In Specific Clinical Settingsmentioning
confidence: 99%
“…However, intermediate-to-high-risk PE patients have significantly longer lysis time than low-and-intermediate-risk PE patients [ 69 ]. High PAI-1, low TAFI, and low α2-antiplasmin indicate a high-risk biomarker profile in acute PE [ 105 ]. This may be of clinical importance when evaluating the results of catheter-based therapy and thrombolysis in PE.…”
Section: Fibrinolysis In Specific Clinical Settingsmentioning
confidence: 99%
“…The pathogenesis of thromboembolism in PE is complex, involving various mechanisms including inflammation, hemostatic dysregulation, fibrinolytic deficit, cellular, and vascular dysfunctions. 3 5 Additionally, risk factors such as obesity, contraceptive use, pregnancy, immobilization, chemotherapy, and anticoagulation also contribute to VTE development. 6 15 Furthermore, genetic predispositions like FV-Leiden, prothrombin gene mutation (G20210), and deficiencies in anti-thrombin III, protein C, and protein S), alongside hyperhomocysteinemia and MTHFR mutation, play significant roles in VTE pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Following thrombin activation, TAFI downregulates fibrinolysis, thus linking the latter with coagulation [ 5 ]. Two pools of TAFI are present in blood, the plasma pool and the platelet pool, which is only secreted upon platelet activation and accounts for less than 0.1% of total blood TAFI [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AtheroGene study also found that the amount of TAFIa is independently associated with the risk of death from cardiovascular causes [ 9 ]. Notably, in the context of acute pulmonary embolism (PE), low TAFI concentrations and low alpha-2-antiplasmin correlated with worse PE severity [ 7 ]. Yet, other studies have reported opposing findings as to TAFI levels in the aforementioned disease categories.…”
Section: Introductionmentioning
confidence: 99%